Determinants of utilization of health services - Arora, Manisha; Koshy, George; Gangadharan, Vandana (International Journal Of Community Medicine And Public Health, 2019)
Background: Health care in India is a complex amalgam involving various stakeholders. For decades it has been a neglected area with reluctance in increasing the inputs such as finance or infrastructure required to drive this system. Utilization and access to this health system is a key indicator and major determinant of health seeking behaviour. Methods: This community based cross sectional study was conducted from January-February 2016 in, the urban slum located in a metro city using a pretested, semi-structured questionnaire. The data was analyzed using SPSS 22. Results: More than half of the participants preferred to seek treatment from a public health care facility compared to a private. One of the most predominant determining factors on choosing a particular health facility was affordability. Main barriers perceived in utilization of health services were long waiting time at the health facility and expenditure on treatment. Conclusions: The key for ensuring adequate and appropriate utilization of health care services is in having an efficient government health care delivery system which can offer quality and affordable medical care to one and all.